Bibles, Ballots, and Bills: Political Resistance to Parochial Education in 1870s Ohio - Gutowski, James A. (US catholic historian, 2018)
The post-Civil War era opened a new chapter in the development of Catholic education in the United States. Seeking ways to forge stronger bonds of national unity, the Republican Party placed a high priority on public education as a means of forging a common American culture. Subsequently, members of the party viewed the growing number of Catholic schools, which offered an alternative to the public system, as a threat. The disproportionate growth of the Catholic population in Ohio alarmed the Republican Party, then holding many local and statewide offices. These officials sought to create legal and legislative barriers to hinder the influence of the Catholic Church, resulting in a defined wall of separation between public and parochial education in the state which would last for more than a hundred years.